The dynamics of language and inequality in education social and symbolic boundaries in the global south - Joel A. Windle; Lesley Bartlett; Dánie Marcelo de Jesus (Bristol : Multilingual Matters, 2020)
"This book contributes new perspectives from the global south on the ways in which linguistic and discursive boundaries shape inequalities in educational contexts, ranging from Amazonian missions to Mongolian universities, using critical ethnographic and sociolinguistic analyses."-- Provided by publisher
Keywords: Developing countries; Language and education Developing countries Case studies; Educational equalization Developing countries Case studies